Mediating Role of Strategy in the Relationship between Organization Learning and Business Performance - Savitri, Fania Mutiara; Indarto, Indarto (JURNAL STUDI MANAJEMEN ORGANISASI, 2020)
Business performance was always associated with small and medium scale businesses durability. Wedding Organizer (WO) Business was a seasonal business with poor durability characteristic due to wedding events fluctuation. WO business role was crucial both helping and organizing wedding event that is ussualy needed by the bride and groom in their wedding. This study aimed to analyze the impact of organizational learning on business performance and use collaboration and business diversification as mediating variable in Semarang Wedding Organizer. Research approach used quantitative research method. This research type is an explanatory research in explaining factors that affect business performance. This study took a sample 43 respondents who run Wedding Organizer business in Semarang City by convenience sampling method. Data was collected through a questionnaire with a Likert scale measurement with five measurement scales. Data analysis method uses 3-stage multiple regression using SPSS 20. The results of this study proved that organizational learning affects collaboration, organizational learning affects business performance; Organizational learning does not affect business diversification, collaboration affects business performance and diversification does not affect business performance. The mediation test also explained that collaboration was successful as a mediating variable on research conducted at Semarang Wedding Organizer. This result also give a new concept called collaboration-based project strategy.